Comorbidity and its Impact on Mortality of COVID-19 in Yazd Province, a Central Part of Iran: a Hospital-Based Study - Moslem Taheri Soodejani; Saeed Hosseini; Reyhane Sefidkar; Farzan Madadizadeh; Hossein Fallahzadeh; Ahmad Dehghan; Neda Dehghani Tafti; Mohammad Hassan Lotfi (Shahid Sadoughi University of Medical Sciences, 2022)
Abstract Introduction: The World Health Organization on March 11, 2020 declared the outbreak of severe acute respiratory syndrome Corona virus 2 disease (COVID-19) a pandemic situation. The main aim of this study was investigating mortality of COVID 19 by considering chronic diseases. Materials and methods: this study was conducted as a cross-sectional in which all confirmed cases were examined. The variables considered in this study were age, sex, diabetes mellitus, cancers, hypertension, heart diseases, kidney diseases, and liver diseases. Independent sample t test, Chi-square and binary logistic regression were used to data analysis. All statistical analysis was done in SPSS 16 and significant level was set at 0.05. Results: Out of 22849 PCR and CT scan tests, 16061 ones were positive. According to the confirmed cases, prevalence of COVID-19 was calculated about 0.019. Also hospital case fatality rate and mortality rate were calculated 156 and about 8.2 per 100000 respectively.  Hypertension, and age had significant relationship with morbidity of COVID-19, in other hand, age (OR: 4.51, p<0.001), kidney diseases (OR: 1.84, p<0.001), diabetes mellitus (OR: 1.31, p<0.001), cancer (OR: 2.73, p<0.001), liver diseases (OR: 2.27, p<0.001) had impact on mortality of covid-19. Population Attributable Fraction (PAF) showed that diabetes mellitus, cancers, kidney diseases, and liver diseases had 4.2, 2.4, 1.3, and 0.2 percent, respectively. Conclusion: age and some underlying diseases increase odds of death due to COVID-19. It seems that preventing high-risk people from being infected is an effective solution to reduce COVID-19 death rate. To do this, health protocols need to be implemented more seriously for these sensitive groups.